2014
DOI: 10.1063/1.4885139
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of H2 Eley-Rideal abstraction from W(110): Sensitivity to the representation of the molecule-surface potential

Abstract: Dynamics of the Eley-Rideal (ER) abstraction of H 2 from W(110) is analyzed by means of quasiclassical trajectory calculations. Simulations are based on two different molecule-surface potential energy surfaces (PES) constructed from Density Functional Theory results. One PES is obtained by fitting, using a Flexible Periodic London-Eyring-Polanyi-Sato (FPLEPS) functional form, and the other by interpolation through the corrugation reducing procedure (CRP). Then, the present study allows us to elucidate the ER d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 103 publications
(143 reference statements)
1
58
0
Order By: Relevance
“…These areas differ from the ones from previous works 45,46,49 because it was found that few ER recombination events occur for trajectories starting outside of the smaller sampling area previously used. Nevertheless, despite some quantitative differences between the present and the previous results, all the conclusions remain.…”
Section: Theoretical Methodsmentioning
confidence: 66%
“…These areas differ from the ones from previous works 45,46,49 because it was found that few ER recombination events occur for trajectories starting outside of the smaller sampling area previously used. Nevertheless, despite some quantitative differences between the present and the previous results, all the conclusions remain.…”
Section: Theoretical Methodsmentioning
confidence: 66%
“…The former mechanism involves direct collision between a scattering atom (projectile) and an adsorbed species (target), 30 while the latter is governed by hyperthermal diffusion of the projectile onto the surface prior to abstraction. 31 The influence of the crystal face has been recently scrutinized theoretically for the Eley-Rideal (ER) recombination a) pascal.larregaray@u-bordeaux.fr of hydrogen and nitrogen on the W(100) and W(110) surfaces, [32][33][34][35][36] accounting for dissipation to surface phonons and electrons. 37 In these direct ultrafast processes, the surface is thought to mostly behave as a spectator.…”
mentioning
confidence: 99%
“…Since the actual fate of such trajectories is unknown, the corresponding contribution is taken as an uncertainty to any possible outcome of scattering. 35,36,43 The vibration of the formed H 2 molecules has been semiclassically quantized via the Gaussian weighting procedure. [57][58][59] In order to rationalize nonadiabatic effects upon scattering, molecular dynamics simulations are performed within the Born-Oppenheimer static surface (BOSS) approximation and within the local density friction approximation (LDFA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31 In addition, the single adsorbate study has been here performed with FPLEPS PES, whereas the multiadsorbate potential was developed from a CRP PES, which leads to higher ER reactivity as previously investigated. 29 The influence of isotope effects observed in single adsorbate studies is also present here. Homonuclear combinations of isotopes lead to similar cross sections, whereas the reactivity for heteronuclear combinations is ordered by the (m p /m t ) ratio.…”
Section: ■ Dynamics Results and Discussionmentioning
confidence: 95%